Retinal detachment after silicone oil removal is prevented by 360° laser treatment. Issue 11 (9th September 2008) - Avitabile, T; Longo, A; Lentini, G; Reibaldi, A
Abstract : Aim: To investigate the effect of 360° laser retinopexy on the incidence of retinal detachment (RD) after silicone oil removal. Methods: In a prospective, randomised clinical trial, 303 patients (303 eyes) affected with primary (n = 211) or recurring (n = 92) rhegmatogenous RD treated by vitrectomy with silicone oil (1000 cSt) and endolaser photocoagulation of retinal breaks were randomised to receive 360° laser retinopexy or not. After at least 4 months, in eyes with a fully attached retina, the silicone oil was removed. The incidence of RD after silicone oil removal was evaluated. Results: 151 eyes received 360° laser retinopexy (completed intraoperatively in 93 eyes and postoperatively in 58 eyes, in nine of them after cataract extraction); 152 eyes served as controls. Silicone oil was removed from 139 laser-treated eyes (92.05%) and 129 controls (84.87%; NS). In the first group, 12 eyes (8.63%) developed an RD posterior to laser treatment (including the macula), three eyes (2.16%) had a localised posterior RD (treated by laser), and 14 (10.07%) had an RD anterior to the laser treatment. In the control group, RD occurred in 27 eyes (20.93%; p  =  0.007). Conclusions: 360° laser retinopexy reduces the incidence of RD after silicone oil removal; it should be completed intraoperatively.